Sintesis dan karakterisasi magnetit terlapis dimerkaptosilika - Ngatijo; Abdurrazaq Habib; Diah Riski Gusti (CHEMPUBLISH JOURNAL, 2019)
Synthesis of dimerkaptosilica coated magnetite was carried out in several stages, namely synthesis of magnetite from FeCl3.6H2O and FeSO4.7H2O by coprecipitation method. Extraction of sodium silicate from rice husk ash as a source of silica. Coating magnetite by dimerkaptosilica using 2,3-dimercapto-1-propanol as a source of mercapto groups and sodium silicate as sources of silica. Coating is done by the sol-gel method. FTIR characterization showed the appearance of uptake at wave numbers 894,04 cm-1, 2951,22 cm-1 and 3655,26 cm-1 from several absorbances which also appeared in magnetite material spectra indicating ―SH, ―CH2 and ―OH groups. XRD characterization was characterized by the appearance of a peak at 2θ, which was 35,43° and SEM characterization showed that the material Fe3O4―DMS had a morphological shape in the form of round clumps forming gray-colored aggregates.